2021
DOI: 10.3390/jtaer16070169
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cryptocurrency Trading Websites on Airlines’ Advertisement Campaigns

Abstract: In future years, airline companies will be leaning more and more towards cryptocurrencies to implement their digital marketing strategies as leaders seek to gain an understanding of the factors affecting airlines’ visibility parameters. Cryptocurrency investment websites are currently experiencing rising demand, making them an appropriate site for paid advertisements. The above factors suggest the need for airlines to harvest cryptocurrency investment and platform users in their favour. To this end, it can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…But some authors are also studying the technologies and processes to tie digital marketing and supply chain management (Ardito et al , 2019) or even to evolve DDM from the firm’s boundaries to the policy research and the big societal trends, such as poverty, sustainability, health or education (Sheth and Kellstadt, 2021). Big data, hereby understood as the sum of structured and unstructured data that feeds modern DDM, has also been studied in the context of resource-based view (RBV) theory, where knowledge, that is extracted from data, is considered a key resource (Akter et al , 2021) and research included in this cluster shows the strategic pathway in the big data spectrum toward knowledge a valuable resource (Sakas et al , 2021). The firms exploring big data often fail to attain better performance and the promised advantages (De Luca et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…But some authors are also studying the technologies and processes to tie digital marketing and supply chain management (Ardito et al , 2019) or even to evolve DDM from the firm’s boundaries to the policy research and the big societal trends, such as poverty, sustainability, health or education (Sheth and Kellstadt, 2021). Big data, hereby understood as the sum of structured and unstructured data that feeds modern DDM, has also been studied in the context of resource-based view (RBV) theory, where knowledge, that is extracted from data, is considered a key resource (Akter et al , 2021) and research included in this cluster shows the strategic pathway in the big data spectrum toward knowledge a valuable resource (Sakas et al , 2021). The firms exploring big data often fail to attain better performance and the promised advantages (De Luca et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This practically means that visitors clicked the advertisement and entered accidentally, and this underlines the finding of the first hypothesis. The fourth hypothesis (H4) found a correlation between the time spent on the website, the visibility, and the paid traffic, as presented in the visibility optimization scenario in Section 3.2.1, and on the execution of the agent-based model in Section 3.3, the paid advertisements (social and general) have a beneficial impact on corporate websites' traffic and visibility [14,16,92,93]. Finally, the findings for the fifth hypothesis (H5) were very interesting.…”
Section: Discussionmentioning
confidence: 96%
“…Results have shown that for cryptocurrency trade organizations to achieve an innovative refinement of their organic and paid traffic campaigns, website digital behavior metrics should be examined. These results could provoke enhanced website visibility [66] and campaign strategical cost degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Web Analytics, combined with suitable KPIs selection, give major assistance to organizations' sustainability, profitability [17]- [18], and digital brand name [66] enhancement. Cryptocurrency trade organizations organic and paid traffic strategies can be utterly benefited and refined by being customized to reflect digital behavior metrics variation.…”
Section: B Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation